Leveraging global climate finance for sustainable forests: Opportunities and conditions for successful foreign aid to the forestry sector - Unai Pascual; Eneko Garmendia; Jacob Phelps; Elena Ojea (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Forest loss and degradation remains a leading environmental problem. The long history of sustainable forest management has often failed to meet expectations - constrained by funding, governance, capacity and competing interests. Initiatives from the climate change policy arena are opening new ways for a broader mainstreaming of forest management, specially through foreign aid mechanisms towards Reducing Emissions from Deforestation and Forest Degradation (REDD+). This paper addresses key questions regarding the potential of REDD+ to support sustainable forest management in the context of complex, multiple stakeholder interests and negotiations, including those of local resource users and international donors.
Keywords: O13; Q23; Q54; Q56; Q57; 330; sustainable forest management; foreign aid; official development assistance; climate change finance; REDD+; forestry sector governance